An experimental study on liquid fuel atomization - J. Ochman; W. Bialik; S. Gil (Metalurgija, 2015)
In the analysis of fuel spray macrostructure, nozzle flow characteristics, their spray angles, liquid distribution in the droplet stream and the stream extent were determined. The investigations were performed with the use of an isothermal measurement station, designed for the study purposes, which enables fuel atomization at a mass flow rate of 1,5 to 15 kg h-1 and the temperature of up to 120 °C. For the measurements, waste oil was selected as the medium spray due to its significant viscosity fluctuations with temperature. The atomization overpressure and temperature ranges were within 0,5 to 1,0 MPa and 20 °C to 115 °C, respectively. The liquid stream radial intensity distribution for the 50 mm and 100 mm distances from the fuel nozzle and the overpressure of 0,8 MPa, 1,0 MPa at a stable temperature of 60 °C were measured.